Pengaruh Rotasi Pekerjaan Dan Motivasi Kerja Terhadap Kinerja Karyawan Padadivisi Sbu Perkapalan PT Pusri Palembang - Yussi Rapareni (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2018)
The purposeof this research is to know the influence of working rotation and motivation to employee performance in Division of SBU Perkapalan PT Pusri Palembang. The respondents are the whole permanent employee which is 75 people. The whole populations are used as sample with census technique. Data collection tool used by questioner and analysis method used is double linear regression with the help program SPSS 17.0.According double linear regression test obtained Y= 0,746 +0,639X1+0,348X2can be explained that working rotation and motivation have positive coefficient and significant to employee performance. From determination coefficient test obtained Rsquare (R2) value 0,993 (99,3%) which means the influence of working rotation and motivation to the employee performance are very closely.